Optimization of damping effect for the air spring by the frequency dependent orifice - Yuichiro TAKINO (The Japan Society of Mechanical Engineers, 2017)
This study proposes a newly developed structure for a frequency-dependent orifice for an air spring of a passenger train vehicle. This frequency-dependent orifice reduced both the rolling motion and the vertical vibration at high frequency. This paper also presents the numerical simulation results. Optimal settings of the springs and dampers of the bogie are essential for reducing the uncomfortable carbody motion while the train is running. The air springs provide insulation and damping through air compressibility in the bellows and pressure loss of the airflow passing through an orifice installed between the air spring and the auxiliary reservoir. The frequency characteristics of a standard air spring show a peak at a frequency of ~1 Hz of the rolling motion of the carbody. A smaller orifice seems to be one of the solutions to change this characteristic. However, this method worsens the damping property at high frequency. To solve this problem, a frequency-dependent orifice with active vibration control technology has been proposed. This orifice improves the vertical vibration at low frequencies and the rolling motion of the carbody; however, it does not improve the properties at high frequencies. The results of our previous research left issues such as the need to improve the high-frequency response in a future study. The results of this study show that our newly developed frequency-dependent orifice effectively reduces the vertical vibration at high frequency with no external power supply. We are planning further simulations including realistic disturbance and a running test using a prototype of the frequency-dependent orifice.